Flavonoids as Therapeutic Agents in Alzheimer's and Parkinson's Diseases: A Systematic Review of Preclinical Evidences. (10th May 2018) - de Andrade Teles, Roxana Braga; Diniz, Tâmara Coimbra; Costa Pinto, Tiago Coimbra; de Oliveira Júnior, Raimundo Gonçalves; Gama e Silva, Mariana; de Lavor, Érica Martins; Fernandes, Antonio Wilton Cavalcante; de Oliveira, Ana Paula; de Almeida Ribeiro, Fernanda Pires Rodrigues; da Silva, Amanda Alves Marcelino; Cavalcante, Taisy Cinthia Ferro; Quintans Júnior, Lucindo José; et al.
Abstract : Alzheimer's and Parkinson's diseases are considered the most common neurodegenerative disorders, representing a major focus of neuroscience research to understanding the cellular alterations and pathophysiological mechanisms involved. Several natural products, including flavonoids, are considered able to cross the blood-brain barrier and are known for their central nervous system-related activity. Therefore, studies are being conducted with these chemical constituents to analyze their activities in slowing down the progression of neurodegenerative diseases. The present systematic review summarizes the pharmacological effects of flavonoids in animal models for Alzheimer's and Parkinson's diseases. A PRISMA model for systematic review was utilized for this search. The research was conducted in the following databases: PubMed, Web of Science, BIREME, and Science Direct. Based on the inclusion criteria, 31 articles were selected and discussed in this review. The studies listed revealed that the main targets of action for Alzheimer's disease therapy were reduction of reactive oxygen species and amyloid beta-protein production, while for Parkinson's disease reduction of the cellular oxidative potential and the activation of mechanisms of neuronal death. Results showed that a variety of flavonoids is being studied and can be promising for the development of new drugs to treat neurodegenerative diseases. Moreover, it was possible to verify that there is a lack of translational research and clinical evidence of these promising compounds.